Етапи розвитку та напрями досліджень в Інституті металофізики ім. Г. В. Курдюмова НАН України - Івасишин, О.М.; Лень, Є.Г.; Надутов, В.М.; Татаренко, В.А. (Металлофизика и новейшие технологии, 2016)
Дано короткий історичний нарис створення та основних етапів розвитку Інституту металофізики ім. Г. В. Курдюмова НАН України, якому у 2015 році виповнилося 70 років. Стисло викладено основні наукові напрями та досягнення вчених-металофізиків Інституту за останні десятиліття та зазначено перспективні напрями металофізичних досліджень в Україні. Дан краткий исторический очерк образования и основных этапов развития Института металлофизики им. Г. В. Курдюмова НАН Украины, которому в 2015 году исполнилось 70 лет. Кратко изложены основные достижения учёных-металлофизиков Института за последние десятилетия и указаны перспективные направления металлофизических исследований в Украине. A short historical review of stages of formation of the G. V. Kurdyumov Institute for Metal Physics (at the NAS of Ukraine) in connection with its seventieth anniversary is presented. (According to both the decree of the Council of Peoples Commissars of the Ukrainian SSR of 15 November, 1945 and the decision of Presidium of the Academy of Sciences of the Ukrainian SSR of 21 December, 1945, Laboratory of Metal Physics (at the Academy of Sciences of the Ukrainian SSR) began to work since 1 January, 1946.) The basic achievements of metal physicists of the Institute along the past decades are briefly identified, and promising trends of metal physics research in Ukraine are outlined.